Assessing feasibility and maternal acceptability of a biomechanically-optimized supine birth position: A pilot study. - Lisa Bouille (Public Library of Science (PLoS), 2021)
Background In order to manage a protracted second stage of labor, "eminence-based" birth positions have been suggested by some healthcare professionals. Recent biomechanical studies have promoted the use of an optimized supine birthing position in this setting. However, uncertainty exists regarding the feasibility of this posture, and its acceptability by women. This pilot study primarily aimed to assess these characteristics. Objective and methods In this monocentric prospective study, 20 women with a protracted second stage of labor were asked to maintain a biomechanically-optimized position for at least 20 minutes at full dilatation. This posture is similar to the McRoberts' maneuver. Maintaining the position for 20 minutes or more was considered clinically relevant and indicative of feasibility and acceptability. Satisfaction with the position was assessed using a Visual Analogue Scale (VAS). A sub-group analysis was performed to assess eventual differences between more and less satisfied patients, according to the median of patients' satisfaction scores. Results Seventeen patients (85%) maintained the optimized position for at least 20 minutes. The median satisfaction score of these participants was 8 (interquartile range: 1) out of 10. No significant differences were found between the two sub-groups (satisfaction score <8 vs satisfaction score ≥8) regarding general and obstetric characteristics, as well as obstetrical and fetal outcomes. Conclusion The optimized position is acceptable and feasible for women experiencing a protracted second stage of labor. Further clinical studies are needed to assess the efficiency of such positions when women undergo an obstructed labor.